Indonesia and Africa: the xylophone as a culture-indicator - Jones, A. M. (International Library of African Music, 1960)
This essay is an appeal to scholars of various disciplines to bring their knowledge to bear on a thesis which has arisen in the first place purely from musical evidence. The thesis we have propounded alters our perspective of Africa; it calls for a map with the Indian Ocean in the centre—a basin whose rim is Indonesia on the east, Madagascar in the south, and Africa on the west, all, to a greater or less extent, sharers in a common sphere of influence. The theory calls for the collaboration of scholars working all round this rim. Perhaps African studies have tended to be too much confined to Africa, though we believe other workers are now also looking tentatively at Indonesia. Let us all come into the open with evidence for or against. We would welcome discussion and criticism, but, as a musician, with one caveat, that those who would demolish the non-musical evidence must at the same time account for the musical phenomena if their argument is to stand.
Keywords: Ethnomusicology; Music; Chopi (African people); Xylophone music; Xylophone; Africa; Adangme (African people); Yoruba (African people); Musical instruments; Yoruba Art; Indonesia; African Music; Xylophone (Instrument)